"Friendship, but Bloke-ier": Can Mateship Be Reimagined as an Inclusive Civic Ideal in Australia?. Issue 2 (3rd April 2022) - Carlin, Na'ama; Jones, Benjamin T.; Laugesen, Amanda
ABSTRACT: In 1999, John Howard attempted to insert the word "mateship" into the Constitution, arguing that it had been reimagined as an inclusive national ideal. This article looks at the history and meaning of mateship, followed by a discussion of contemporary Australian attitudes towards it. The data we use in this article is from a voluntary survey (the Australian Mateship Survey) conducted by the authors, which asked respondents ( N  = 576) how they define mateship and how they feel about the term. The results indicate that a majority think mateship is a key feature of Australian identity but have concerns when the idea is politicised. A sizable minority believe the term is gendered and racialised and, therefore, is not inclusive of all Australians. Further, the survey suggests that a wide range of opinions exists even among those who do believe mateship has national significance. Twenty years after Howard's attempt to enshrine mateship in the Constitution, this article suggests that the concept remains too divisive to serve as a core Australian value.